Open source and journalism: toward new frameworks for imagining news innovation. - Lewis, Seth C; Usher, Nikki (Media, Culture & Society, 2013)
Journalists and technologists increasingly are organizing and collaborating, both formally and informally, across major news organizations and via grassroots networks on an international scale. This intersection of so-called ‘hacks and hackers’ carries with it a shared interest in finding technological solutions for news, particularly through open-source software programming. This article critically evaluates the phenomenon of open source in journalism, offering a theoretical intervention for understanding this phenomenon and its potential implications for newswork. Building on the literature from computer science and journalism, we explore the concept of open source as both a structural framework of distributed development and a cultural framework of pro-social hacker ethics. We identify four values of open-source culture that connect with and depart from journalism—transparency, tinkering, iteration, and participation—and assess their opportunities for rethinking journalism innovation.